Marriage Tradition of Marlojong in Community of Mandailing Natal District (Study of Islamic and Positive Law Implementation) - Kasman Kasman; Yasir Nasution; Pagar Pasaribu (Budapest International Research and Critics University, 2019)
This study is aimed to describe the marriage tradition of Marlojong in community of Mandailing Natal District. This study focuses on study of Islamic and positive law implementation of the marlojong. This study is conducted by using descriptive qualitative approach because this study is to understand phenomena related to the implementation of marriage law in a natural setting of society, to understand a phenomenon based on information data obtained from informants. The result shows that there are there motivations of marlojong marriage implementation in Mandailing Natal District. First because they were unable to pay the dowry / tuor requested by the parents of the girl. Second, because they were not allowed to get married. Third, because they avoided the costs of implementing the marriage customs. The implementation of marlojong marriage in the Mandailing Natal community does not contradict the provisions of Islamic law. Pillars and marital conditions are met in accordance with the provisions of Islamic law. So that the marlojong marriage carried out by the Mandailing community is legal according to Islamic Law. The implementation of Marlojong marriage to the Mandailing Natal community according to Positive Law in Indonesia is legal because it does not violate the material requirements and formal requirements that have been determined in Law No. 1 of 1974 concerning Marriage and Compilation of Islamic Law.